THE IMPORTANCE OF APPLYING ACCOUNTING TO THE ISTIQAMAH SIMAWANG ISLAMIC BOARDING SCHOOL - Sri Adella Fitri; Yuza Afina; Tari Durti; Suci Putri Ayu; Steffani Amelia; Rahmad Dani (STIESA Press, 2023)
The purpose of this research is to find out how accounting is applied at the Istiqomah Simawang Islamic Boarding School with reference to ISAK 35 which regulates the presentation of non-profit organization financial statements. Presentation of financial statements includes balance sheet and statement of comprehensive income, statement of changes in net assets, cash flow and notes to financial statements. Research at the Istiqomah Simawang Islamic boarding school shows that Islamic boarding schools use Islamic boarding school accounting guidelines in preparing financial reports.